2023
DOI: 10.1002/xrs.3335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analysis volume in total reflection X‐ray fluorescence analysis

Abstract: Total reflection X‐ray fluorescence (TXRF) is widely used for trace elemental analysis, wherein a thin monochromatic X‐ray beam is typically applied at glancing angles. The actual volume of the sample measured by the instrument (analysis volume) depends on the dimensions of the X‐ray beam and glancing angle, and it is a key feature in sample preparation for TXRF analysis. Herein, the analysis volume, including the analysis region and analysis height, was experimentally evaluated. A thin Au layer approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The optimal dimensions of a TXRF spectrometry specimen were evaluated by Tsuji et al 54 Mask vacuum evaporation was used to prepare a thin circular gold layer at specific positions on a flat glass substrate. By visualising the Au intensity over the glass substrate, it was concluded that a diameter of 5 mm could be detected.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%
“…The optimal dimensions of a TXRF spectrometry specimen were evaluated by Tsuji et al 54 Mask vacuum evaporation was used to prepare a thin circular gold layer at specific positions on a flat glass substrate. By visualising the Au intensity over the glass substrate, it was concluded that a diameter of 5 mm could be detected.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%
“…They determined the change of the FOV at four different excitation angles. 12 The picoliter approach applied here simplies the procedure for determining the detector FOV. It allows positioning the deposits more precisely using motorized stages, which allow for independent movement in the x-, y-and z-directions.…”
Section: Introductionmentioning
confidence: 99%
“…Various commercially available TXRF instruments have been developed; therefore, it is important to determine the analysis area for each TXRF instrument. We have previously determined the analytical area measured using a NANOHUNTER-II TXRF instrument (Rigaku Co., Japan) to be approximately 4 × 5 mm 2 ; 15 therefore, we believe that the optimal APPJ-treated area should be smaller than this value. In addition, it is important to evaluate the retention time of hydrophilicity after APPJ treatment.…”
Section: Introductionmentioning
confidence: 99%